2013
DOI: 10.1165/rcmb.2012-0485oc
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Brush Cells of the Trachea. A Stable Population in a Dynamic Epithelium

Abstract: Tracheal brush cells (BCs) are specialized epithelial chemosensors that use the canonical taste transduction cascade to detect irritants. To test whether BCs are replaced at the same rate as other cells in the surrounding epithelium of adult mice, we used 5-bromo-2'-deoxyuridine (BrdU) to label dividing cells. Although scattered BrdU-labeled epithelial cells are present 5-20 days after BrdU, no BCs are labeled. These data indicate that BCs comprise a relatively static population. To determine how BCs are gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 49 publications
1
63
0
Order By: Relevance
“…1B). This result suggests that nasal SCCs, like tracheal brush cells, are capable of producing ACh for release onto nerve fibers (16,17).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…1B). This result suggests that nasal SCCs, like tracheal brush cells, are capable of producing ACh for release onto nerve fibers (16,17).…”
Section: Resultsmentioning
confidence: 88%
“…1A) (6)(7)(8). In the trachea, a related cell type, the chemosensory brush cell, releases acetylcholine (ACh) to activate vagal pain fibers (16)(17)(18), suggesting ACh as a candidate neurotransmitter for SCCs. Similarly, SCCs lining the vomeronasal duct of mice express choline acetyltransferase (ChAT), the synthetic enzyme of acetylcholine (19).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several key studies have demonstrated that specific populations of cells in the mammalian airway epithelia can be directly activated by inhaled "bitter" irritants, which include ciliated epithelial cells in lower (5) and upper airways (6), brush cells (7,12), and airway smooth muscles (4). In spite of this significant progress, the cells and receptors that mediate the response of human airways to the majority of volatile chemicals in health or disease are still largely (20,50).…”
Section: Discussionmentioning
confidence: 99%
“…Other cells with chemosensory functions in mammalian airways are the cholinergic "brush cells" (7)(8)(9)(10). These cells are present in the upper and lower airways in mammals, where they play roles such as controlling of breathing in rodents (11) and the epithelial response to bacterial compounds and other harmful chemical stimuli (12).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Although the formation of cytoneural junctions is generally regarded as unlikely, the close association of fibers with epithelial cells is strongly suggestive of the presence of afferent signaling (43). The chemical mediator for signaling between PNECs and vagal afferents is not known but may be ATP (43)(44)(45), which would be consistent with recent clinical studies of cough (46). The PGP9.5-immunonegative fibers we observed had fiber diameters that suggest they are A delta fibers and, despite the widely held belief that PGP9.5 is a panneuronal marker, some unpublished observations demonstrate PGP9.5-immunonegative nerves in human nodose ganglia (A. Myers, private communication).…”
Section: Observationsmentioning
confidence: 99%